Driving Factors Of Intellectual Capital In A Literature Review - Kasir, Kasir (Universitas Indonesia Membangun, 2025)
This research is in the form of a literature review in the field of financial accounting which aims to determine what factors are influenced by intellectual capital and how the research results are. This research employs a qualitative method utilizing a literature approach via a literature review. Where the articles studied were 43 articles sourced from emerald.com, elseiver.com, springer.com, googleschoolar.com and other websites by filtering research titles and using the keyword